Virtual Scoping: lightweight and scalable TSN time synchronization accuracy measurement method - SUN Yinhan; SUN Zhigang; FU Wenwen; LI Wenchao; HUANG Rong (Tongxin xuebao)
Aiming at the problems of existing time synchronization accuracy measurement methods based on clock pulse, such as complex measurement system composition, limited measurement scale by the number of instrument acquisition interfaces, and inability of measurement data to support real-time network management and control, a lightweight and scalable time synchronization accuracy measurement method called Virtual Scoping (VS) was proposed based on the centralized management and control architecture of time-sensitive networking (TSN). Ability to virtualize oscilloscope functions in the network control plane. Firstly, the parameter DriftTime was defined by the method, which could be used to accurately estimate synchronization accuracy. This parameter was calculated from protocol status data such as synchronization message transmission timestamps, residence delay, and link delay. Finally, the V-Scope tool was implemented in the network control plane and deployed in a prototype system built on the OpenTSN open-source project for experimentation. The results demonstrate that V-Scope exhibits only nanosecond-level errors compared to measurements obtained from professional testing equipment. Additionally, the feasibility and advantages of the VS method in supporting network management functions are discussed. As an example of accuracy optimization, a frequency offset compensation algorithm based on V-Scope is designed and implemented, which improves the synchronization accuracy of the prototype system by 32.3%.